2017
DOI: 10.1590/0001-3765201720170118
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric bioreduction of β-ketoesters derivatives by Kluyveromyces marxianus: influence of molecular structure on the conversion and enantiomeric excess

Abstract: This study presents the bioreduction of six β-ketoesters by whole cells of Kluyveromyces marxianus and molecular investigation of a series of 13 β-ketoesters by hologram quantitative structure-activity relationship (HQSAR) in order to relate with conversion and enantiomeric excess of β-stereogenichydroxyesters obtained by the same methodology. Four of these were obtained as (R)-configuration and two (S)-configuration, among them four compounds exhibited >99% enantiomeric excess. The β-ketoesters series LUMO ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…K. marxianus is also distinguished by thermotolerance (Lane et al, 2011 ), and the fastest reported growth rate of any eukaryote (Groeneveld et al, 2009 ). Recent years have seen increasing interest in new applications such as production of biomolecules (Hughes et al, 2017 ; Lin et al, 2017 ), biocatalysis (Oliveira et al, 2017 ; Wang et al, 2017 ) and heterologous protein production (Gombert et al, 2016 ; Lee et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…K. marxianus is also distinguished by thermotolerance (Lane et al, 2011 ), and the fastest reported growth rate of any eukaryote (Groeneveld et al, 2009 ). Recent years have seen increasing interest in new applications such as production of biomolecules (Hughes et al, 2017 ; Lin et al, 2017 ), biocatalysis (Oliveira et al, 2017 ; Wang et al, 2017 ) and heterologous protein production (Gombert et al, 2016 ; Lee et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…marxianus is also distinguished by its thermotolerance [36,87] and the highest growth rate in eukaryotes [88]. In recent years, interest also increased in several new applications such as production of biomolecules [89,90], biocatalysts [91,92], and heterologous protein expression [93,94].…”
Section: Complete Genome Sequence Of Thermotolerant Yeast K Marxianumentioning
confidence: 99%